Inhibition of Oocyte Maturation by Malathion and Structurally Related Chemicals in Zebrafish (Danio rerio) After In Vitro and In Vivo Exposure. (13th April 2022) - Miller, Justin G.P.; Van Essen, Darren; Brinkmann, Markus; Raza, Yamin; Dubiel, Justin; Fujita, Kaden K.; Doering, Jon A.; Wiseman, Steve B.
Abstract: Oogenesis is the process by which a primary oocyte develops into a fertilizable oocyte, making it critical to successful reproduction in fish. In zebrafish ( Danio rerio ), there are five stages of oogenesis. During the final step (oocyte maturation), the maturation‐inducing hormone 17α, 20β‐dihydroxy‐4‐pregnen‐3‐one (MIH) activates the membrane progestin receptor, inducing germinal vesicle breakdown. Using in vitro assays, it has been shown that anthropogenic stressors can dysregulate MIH‐induced oocyte maturation. However, it is unknown whether the in vitro assay is predictive of reproductive performance after in vivo exposure. We demonstrate that a known inhibitor of oocyte maturation, malathion, and a structurally related chemical, dimethoate, inhibit oocyte maturation. However, malaoxon and omethoate, which are metabolites of malathion and dimethoate, did not inhibit oocyte maturation. Malathion and dimethoate inhibited maturation to a similar magnitude when oocytes were exposed for 4 h in vitro or 10 days in vivo, suggesting that the in vitro zebrafish oocyte maturation assay might be predictive of alterations to reproductive performance. However, when adult zebrafish were exposed to malathion for 21 days, there was no alteration in fecundity or fertility in comparison with control fish. Our study supports the oocyte maturation assay as being predictive of the success of in vitro oocyte maturation after in vivo exposure, but it remains unclear whether inhibition of MIH‐induced oocyte maturation in vitro correlates to decreases in reproductive performance. Environ Toxicol Chem 2022;41:1381–1389. © 2022 SETAC Abstract : The ability of oocyte maturation assays to predict reproductive performance in zebrafish. Maturation inducing hormone (MIH) stimulated maturation of oocytes after in vitro exposures to selected chemicals was predictive of the success of oocytes to mature in vitro after in vivo exposure. However, oocyte maturation assays using in vitro exposures were not predictive of reproductive performance during a 21‐day reproduction assay.